Food health and population in development. - Bf, Johnston (Journal of Economic Literature, 1977)
The manifestations of poverty (e.g. nutritional deprivation and ill-health) and the attendant serious obstacle posed by rapid population growth in developing countries are a problematic and serious concern for policy makers responsible for formulating policies and programs that would alleviate such conditions. In many developing countries reduction of poverty is interrelated with other goals (promoting a self-sustaining cumulative economic growth improving health and public services slowing down populating growth rate) bringing about problems related to the multiplicity of options for effective action. Some of these problems involve the limited application of cost-benefit analysis and other conventional investment criteria in measuring benefits derived from health and education programs the influence of political decisions on economic policies and the extent upon which technology and organization affect the success or failure of development goals. Scarce resources limited options and disparate requirements of competing groups also affect the types of programs implemented (especially nutrition and family planning programs with its numerous intervention schemes that have mostly proved disappointing). To improve the health and nutrition of the population and to slow down population growth rates of developing countries it is imperative that economists nutrition and health experts demographers and political scientists collaborate on a multidisciplinary research scheme that would identify and provide guidelines in formulating effective and feasible policies and programs for the well-being of the population.